EFL teachers' attempts at feedback innovation in the writing classroom. (March 2016) - Lee, Icy; Mak, Pauline; Burns, Anne
To date, research on feedback in second language (L2) writing has primarily focused on feedback per se, with little attention paid to the teachers' professional development with regard to feedback in writing. This study aims to explore the ways in which two secondary teachers in Hong Kong attempted to implement feedback innovation in their writing classrooms after receiving some professional development input, as well as the factors that influenced their attempts at feedback innovation. The findings indicate that the teachers were unable to fully translate into practice the feedback principles acquired from teacher education and reveal a string of factors that influenced their attempts at feedback innovation. The study has implications for teacher education and teacher professional development, shedding light on how teachers can be supported to bring innovation to conventional feedback approaches in the writing classroom.